DEVELOPMENT OF QUIZIZZ-BASED PROBLEMS OF LIFE ORGANIZATION SYSTEM MATERIALS FOR CLASS VII JUNIOR HIGH SCHOOL STUDENTS - Noer Af’idah; Dwi Sri Handayani (Program Studi Pendidikan IPA FIP Universitas Hasyim Asy'ari, 2024)
In the 21st century teachers face big challenges on how to implement technological developments into the learning process, so that students become more competent and able to compete according to the times. Assessment in the teaching and learning process is a process for making decisions based on information obtained from measuring learning outcomes. One of the online-based assessments is Quizizz. The purpose of this research is to describe the process of developing material problems on life organizational systems using the quizizz application and to describe the product developed after the process of theoretical and empirical validity. This research uses the ADDIE development model which stands for Analyze, Design, Development, Implementation, and Evaluation. After that, the questions based on quizzes that had been developed were tested for theoretical and empirical validity. Based on the theoretical analysis conducted by expert validators, an average score of 94.64% was obtained with very good criteria. The results of the empirical validity analysis showed that out of 20 items there were 7 valid questions and 13 invalid questions, the reliability value was 0.583 with moderate criteria, discriminating power with an average of 0.343, moderate difficulty level, and good deception function.